Karakteristik Kondisi Sosial Ekonomi Terhadap Perilaku Migrasi di Kabupaten Jeneponto - Abdul Rahman; Armita Kurnia Dewi; Sitti Aisyah; Nurbayani Nurbayani (Al-Buhuts, 2023)
This study aims to determine and analyze the influence of social and economic factors on migration behavior in Jeneponto. By using this type of quantitative research, the data is processed with a type of confirmative research using a quantitative approach. Where the research was carried out in Jeneponto Regency from May to September 2022. The data used is secondary data obtained through the Central Bureau of Statistics and other appropriate sources also related to research. The analysis technique used is the classical assumption test and multiple linear regression with the help of the SPSS Ver 26 program. The results of the multiple linear regression analysis together show that: (1) education has a negative and insignificant effect on migration in Jeneponto Regency (2) income per capita has a negative and significant effect on migration in Jeneponto Regency (3) the regional minimum wage has a positive and significant effect on migration in Jeneponto Regency (4) Agricultural land has a negative and insignificant effect on migration in Jeneponto Regency